Applications of Agent Technology in Traffic and Transportation - Klügl, Franziska.; Klügl, Franziska.; Bazzan, Ana.; Bazzan, Ana.; Ossowski, Sascha.; Ossowski, Sascha. (Whitestein Series in Software Agent Technologies and Autonomic Computing, 2005)
Building effective and user-friendly transportation systems is one of the big challenges for engineers in the 21st century. There is an increasing need to understand, model, and govern such systems at both the individual (micro) and the society (macro) level. Still, this raises significant technical problems, as transportation systems may contain thousands of autonomous, "intelligent" entities that need to be simulated and/or controlled. Therefore, traffic and transportation scenarios are extraordinarily appealing for Distributed Artificial Intelligence, and (multi-) agent technology in particular. This book gives an overview of recent advances in agent-based transportation systems. It includes both a state-of-the-art survey and reports on cutting-edge research in the field.